Towards a sociologically-oriented approach to Enterprise Architecture using the theory of structuration - Mezzanotte, Dominic M., Sr. (My University, 2012)
Enterprise Architecture (EA) describes the process of aligning on organization's business vision, strategy, and business-enterprise information technology (IT) systems into a more efficient, effective, and agile organization. EA defines the processes needed to: Effect an overall organizational transformation by creating, communicating, and improving the key requirements, principles, and models that describe the enterprise's future state; Improve operational efficiency, effectiveness, and stakeholder on-the-job productivity. EA frameworks (EAF) provide a conceptual methodology that supports and guides the engineering, design, and construction effort behind EA. The product of an EAF, an EA plan (EAP), details the infrastructure, requirements, and technical specifications needed to align an organization's strategic business plan and operating model with it's information technology (IT) components and capabilities. Analyzing the philosophy behind today's most popular EAFs (e.g., the Zachman Architecture Framework, The Open Group Architecture Framework (TOGAF), the Federal Enterprise Architecture Framework (FEAF), and the Department of Defense Architecture Framework (DoDAF)) reveals a purely techno-centric, comprehensive, and disciplined approach to EA design. Each framework focuses solely on satisfying the business goals, strategies, and governance of the EA. However, EA transforms the structure, culture, political, and social environment of an enterprise introducing new processes and technologies into the workplace often with unanticipated and unexpected consequences. The organizational transformation that takes place inevitably alters the roles, duties, responsibilities and organizational position of stakeholders with new processes, procedures, and tasks to be learned. This transformation frequently affects stakeholder behavior that can lead to either acceptance or rejection of EA. Our analysis of existing EAFs find them to be deficient in that they fail to address the impact EA has on both organizational transformation and to changes in stakeholder behavior. Failure to address and assess these issues from the framework level as an input to, and result of, an EA frequently manifests itself in stakeholder behavior that limits and/or constrains their participation in EA design. As a result, the EA may fail either partially or completely. This dissertation advances our earlier work exploring three forces that influence EA: organizational transformation, stakeholder resistance to change, and elicitation/use of erroneous EA requirements. We believe each of these issues can be addressed from a sociologically-oriented perspective incorporating ideas from the Theory of Structuration designed to remove barriers that limit stakeholder action. This dissertation aims to implement mechanisms that identify early-on potential roadblocks and negative stakeholder input to the design process and define a more holistic and humanistic oriented framework that assists in motivating stakeholder behavior.
Enterprise Architecture -- Human behavior, organizational transformation, and Enterprise Architecture -- Enterprise Architecture and applying the theory of structuration -- Modeling Enterprise Architecture -- A sociological and humanistic approach to Enterprise Architecture design
(D. Sc.) -- Towson University, 2012.